University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 7 - Practice Exercises - Page 421: 34



Work Step by Step

Separate the differentials and integrate. $\int (\dfrac{e^{2x}+1}{e^x}) dx=\int y^2 dy$ Re-write as: $\int (\dfrac{e^{2x}}{e^x}+\dfrac{1}{e^x}) dx=\int y^2 dy$ This implies that $e^x-e^{-x}+c=(\dfrac{1}{3})y^3+c$ Applying the initial conditions $y(0)=1$, we get Thus, $e^0-e^{-0}+c=(\dfrac{1}{3}) \implies c=\dfrac{1}{3}$ Hence, $\dfrac{y^3}{3}-e^x+e^{-x}-\dfrac{1}{3}=0$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.